179 FEASIBILITY AND ONCOLOGICAL OUTCOME OF CHEMORADIATION WITH INTENSIFIED IMRT IN LOCALLY ADVANCED ESOPHAGEAL CANCER. (14th September 2020) - Innocente, R; Navarria, F; Petri, R; Palazzari, E; Gigante, M; Vecchiato, M; Ziccarelli, A; Martino, A; Foltran, L; Buonadonna, A; Lo Re, G; Spina, M; et al.
Abstract:  : To assess safety, feasibility and efficacy of an intensified preoperative IMRT and concomitant carboplatin and paclitaxel-based chemotherapy (Carbo/Tax CT) in patients (pts) with locally advanced esophageal cancer (LAEC) treated at our Institution. Methods: a retrospective analysis of toxicity (CTCAE 4.03), progression free survival (PFS) and overall survival (OS) of pts affected by LAEC, treated with preoperative intensified radiotherapy (IMRT) and weekly concurrent carboplatin and paclitaxel-based chemotherapy (CT) according to the CROSS trial, between February 2016 and October 2019, at the Centro di Riferimento Oncologico, Aviano (CRO). Results: Sixty-nine consecutive pts, 57(82.6%) males, were treated. The median age was 69 yrs (38–85), the ECOG PS 0–2. All pts underwent concurrent chemoradiotherapy, IMRT technique, 45 Gy/25 to PTV1 (primary tumor volume + regional nodes), a simultaneous boost from 52.5Gy to 54Gy to PTV2 (gross tumor volume) and weekly concurrent carboplatin (AUC2) and paclitaxel (50 mg/m2). Induction CT was administered to 17 pts. All pts completed RT with median 4 (1–5) CT cycles. Median follow-up was 8 months (4–17); 2-yr PFS and OS were 49.0% and 80.3%, respectively. At 2 yrs, local recurrence rate was 8.4% (CI 95%: 2.6%–18.8%). Conclusion: Preoperative intensified IMRT with concomitant Carbo/Tax CT in pts with LAEC appears safe and feasible with promising oncological outcome and needs to be confirmed in a larger series of pts.